Визначення інформації, що містить пропаганду насильства і жорстокості, у контексті статті 300 Кримінального кодексу України - Олішевський, О. В.; Olishevskyi, O. V.; ORCID: http://orcid.org/0000-0003-1102-0675 (Вісник Кримінологічної асоціації України. - 2016. - № 2 (13). - С. 58-67, 2016)
Наведено власне розуміння понять «фізичне, психічне насильство» та «жорстокість». Визначено, які саме відомості або дані належать до інформації, що містить пропаганду культу насильства і жорстокості.

The types of information or data related to information containing propaganda of violence and brutality are not defined. There is no single approach to understanding the researched categories. A number of domestic and foreign scholars have researched the issues related to determining the propaganda of violence and brutality. The authors provided their own definitions of violence and brutality, but they did not reveal the specification of information or data related to information containing their propaganda. The aim of this article is an attempt to analyze the categories of “violence” and “brutality”; to improve the understanding within criminal and legal, criminological aspects; to determine the types of information or data related to information containing propaganda of violence and brutality. Violence must be studied within positive and negative aspects. Criminal and legal science divides violence into physical and mental. Physical violence within criminological aspect – is an illegal influence on bodily integrity, health or life of a person against, beyond, in some cases, according to the will by the way of using physical force of people or animals, technical means, damaging factors and properties of other objects of the material world or various natural phenomena.Psychological violence within criminological aspect – is an illegal influence on the human psyche by the way of submitting information or using technical means, objects of material world, natural phenomena that do not directly affect the health, but the consequence of which is fear, anger, mental disorders or diseases. Brutality within the criminal and legal aspect – is a situationally defined concept, but not completely, thus its content is specified in the process of enforcement by assessing the particular circumstances of the proceedings. Brutality within criminological aspect – is a negative character trait of a person that is defined by indifference to the suffering of others or in pursuit of their cause. The information containing propaganda of the cult of violence and brutality includes information or data of the direct calls for violence and brutality, aimed demonstration in a naturalistic form: causing physical damage to the human body and every living creature (beating, kicking, by blunt objects, cutting off body or body parts, use of weapons, explosives, devices and other items or objects, radiation, electricity, high and low temperatures, pollutants, poison, suffocation, drowning, etc.); escalation of terror, enjoyment of torments, humiliation and suffering details; physiological reactions to injury or pain (martyr’s facial expressions, cries, groans, suffering, blood, agony, etc.); in the action of various torture implements (knives, razors, axes, scissors, cutter, saws, chainsaws, drills, etc.); mockery of corpses; detailed images of the scenes causing physical damage to oneself and suicide; rape or forcible sexual insults in the unnatural way. Taking into account the volume of the researched phenomena, this list can be added.

Дано собственное определение понятий «физическое, психическое насилия» и «жестокость». Определено, какие именно сведения или данные относятся к информации, содержащей пропаганду культа насилия и жестокости.
Determining Information Containing Propaganda Of Violence And Brutality Under The Article 300 Of The Criminal Code Of Ukraine
Определение информации, содержащей пропаганду насилия и жестокости в контексте статьи 300 Уголовного кодекса Украины
Олішевський, О. В. Визначення інформації, що містить пропаганду насильства і жорстокості, у контексті статті 300 Кримінального кодексу України / Олександр Володимирович Олішевський // Вісник Кримінологічної асоціації України. - 2016. - № 2 (13). - С. 58-67.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; насильство; фізичне насильство; психічне насильство; жорстокість; суспільно небезпечна інформація; пропаганда культу насильства і жорстокості; violence; physical violence; mental violence; brutality; socially dangerous information; propaganda of the cult of violence and brutality; насилие; физическое насилие; психическое насилие; жестокость; общественно опасная информация; пропаганда культа насилия и жестокости